Economic theories of Ibn Khaldun from his great work, Muqaddimah - Ogunbado, Ahamad Faosiy; Zein, Ibrahim Mohamed (Postgraduate Student Society IIUM, 2009)
The article deals with the economic theories of the prominent scholar of 14th century, 'Abd ai-Rahman bin Muhammad ibn Khaldun as it was propounded from one of his major works The Muqadimah "Introduction" or "Prolegomena, " which was written as an introduction to "The World History" or Kitab al- 'ibar, wa diwan al-Mubtada' wa al-Khabar. After presenting the icon and some of his works, the paper explains the principal crafts or works, which Ibn Khaldun believes as the most necessary for human existence and necessity for their survival. The Article also explains labour as a source of value in khaldunian's theory, where the concept of rizq "sustenance" is expounded. Division of labour is one of the important concepts in contemporary economics; Ibn Khaldun has discussed it in his landmark book and concludes that cooperation is needed between each division and specialization. The article also touches the theory of demand and supply and relationship between both, which is regarded as determinant factors for the price of commodity in the market as projected in Muqadimmah. The article explores the Theory of Money, its value and its relation to income and expenditure; it provides khaldunian's argument against modern money theory. It also investigates theory of taxation as speculated by Ibn Khaldun. The study is based on library research whereby, books, articles are consulted. Magazines and on-line journal articles are of great use in conducting this study. However, the main reference is Muqaddimah.